PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN PRESTASI BELAJAR - Sulastri (UNIB Press, 2022)
This research was conducted with the aim to find out The application of the STAD cooperative learning model can increase student Sosial skill, The application of the STAD cooperative learning model can improve student learning achievement in Mathematic subjects in Students and The effectiveness of the application of type cooperative learning models STAD in improving student learning achievement in learning Mathematic subjects Class SDN 09 Kota Agung Kabupaten Lahat. The problem in this study is that the learning methods used are less varied, the low attitude of student cooperation in participating in learning. This study used 20 subjects in PTK research, 20 in experimental class research, and 20 people in control class research.Data collection techniques in this study used observation and tests. The results of this study indicate that. The application of a STAD cooperative learning model can increase student cooperation in Mathematic Education subjects. The application of a STAD Social Skill learning model can improve student learning achievement in Mathematic subjects. The application of a STAD cooperative learning model can effectively improve student learning achievement in Islam Religion Education subjects class XII in SDN 09 Kota Agung Kabupaten Lahat